2017
DOI: 10.1007/s10803-017-3028-1
|View full text |Cite
|
Sign up to set email alerts
|

Life Skills Training for Middle and High School Students with Autism

Abstract: This study investigated the extent to which life skills training was offered to middle and high school students with autism and life skills training needs after high school. A secondary analysis of the National Longitudinal Training Study-2 (NLTS-2) data was conducted in this study. This study found that the majority of the middle and high school students with autism (77.4%) had received life skills training in school. Receipt of life skills training differed across students' gender, age, diagnosis of intellec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Given the important benefits of personal development of daily living skills and self‐determination, it is imperative to examine where, what, and how to support their development. Although teaching daily living skills in the natural environment is the most effective method to facilitate generalization, findings from the NLTS‐2 reveal that 85% of instruction occurs exclusively in K‐12 special education classrooms (Chiang, Ni, & Lee, ). The needs of young adults with IDD endures into adulthood, with 80% of individuals classified as having significant problems completing daily living skills independently (Chiang et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the important benefits of personal development of daily living skills and self‐determination, it is imperative to examine where, what, and how to support their development. Although teaching daily living skills in the natural environment is the most effective method to facilitate generalization, findings from the NLTS‐2 reveal that 85% of instruction occurs exclusively in K‐12 special education classrooms (Chiang, Ni, & Lee, ). The needs of young adults with IDD endures into adulthood, with 80% of individuals classified as having significant problems completing daily living skills independently (Chiang et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Although teaching daily living skills in the natural environment is the most effective method to facilitate generalization, findings from the NLTS‐2 reveal that 85% of instruction occurs exclusively in K‐12 special education classrooms (Chiang, Ni, & Lee, ). The needs of young adults with IDD endures into adulthood, with 80% of individuals classified as having significant problems completing daily living skills independently (Chiang et al., ). Identifying effective practices in natural settings to ensure young adults with IDD have equitable access to achieve their independent living goals continues to be a critical need (Nota et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…DLS that are often deficient in adolescents with ASD include personal hygiene, managing medications, doing laundry, preparing meals, using a checking/savings account, budgeting for purchases, and navigating the community (see Duncan et al, 2014). In a recent study, families reported that DLS in the areas of home care, transportation, financial, self-care, relationship, and self-advocacy still needed to be addressed after graduation from high school (Chiang, Ni, & Lee, 2017). Several evidence-based teaching strategies (e.g., technology, video modeling, and behavioral strategies such as reinforcement and prompting) have been identified as effective in teaching adaptive behavior skills, including DLS, to adolescents and young adults with ASD (Bennett and Dukes, 2014;National Autism Center, 2015;Wong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While the Individualized Education Plans (IEPs) of high-functioning adolescents with ASD are required to have transition plans that address goals in the areas of employment, postsecondary education, and independent living, there is often little time to work on these goals, despite the need, because students are often included in regular education classrooms and may have a full academic class load that prevents them from being pulled out for services. One recent study found that high-school students with high-functioning ASD were less likely to receive any life skills training than those with ASD and a comorbid intellectual disability (Chiang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation